Analisis Motivasi, Hard Skill, dan Soft Skill sebagai Penentu Kesiapan Kerja Mahasiswa - Istia, Cicilia Erly; Suryani, Mufid; Septiani, Risa; Nida Nusaibatul Adawiyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Readiness to work is a very crucial aspect in the industrial sector or employment in order to become a professional middle-level workforce and be able to contribute according to their field of expertise. The purpose of this study is to analyze the variables of work motivation, hard skills, and soft skills in influencing the work readiness of students in the Management study program at Gunadarma University. The object of this study is final year students of the management study program. The research method used in this study is multiple linear regression. The sampling technique used is purposive sampling with a sample of 130 respondents. Based on the results of the research conducted, it can be concluded that work motivation, hard skills, and soft skills partially influence work readiness. The most dominant variable influencing work readiness is the soft skill variable.